Morphological diversity and disease severity of Ceratocystis fimbriata on duku (Lansium domesticum) varieties in South Sumatra - Asdhyshani, Muhammad; Muslim, A.; Suwandi; Irsan, Chandra; Hamidson, Harman; Pratama, Rahmat (Current Botany, 2025)
Wilt and stem canker diseases have caused sudden mortality of duku (Lansium domesticum) trees in several major production districts of South Sumatra Province, Indonesia. First reported in 2013, the disease has led to up to 100% tree mortality in severely affected orchards by 2025. The causal species, Ceratocystis fimbriata, was consistently isolated from symptomatic tissues and identified based on morphological characteristics and β-tubulin region analysis. Field observations revealed variation in disease incidence among duku varieties, with lower levels in Ogan Ilir compared to Ogan Komering Ulu Timur, Ogan Komering Ulu Selatan, and Musi Banyuasin. The capacity of this pathogen to infect multiple duku varieties represents a significant threat to the genetic diversity of duku in Indonesia.